Holocene evolution of the Southern Hemisphere westerly winds in transient simulations with global climate models - V. Varma; M. Prange; U. Merkel; T. Kleinen; G. Lohmann; M. Pfeiffer; H. Renssen; A. Wagner; S. Wagner; M. Schulz (Climate of the Past, 2012)
The Southern Hemisphere Westerly Winds (SWW) have been suggested to exert a critical influence on global climate through the wind-driven upwelling of deep water in the Southern Ocean and the potentially resulting atmospheric CO 2 variations. The investigation of the temporal and spatial evolution of the SWW along with forcings and feedbacks remains a significant challenge in climate research. In this study, the evolution of the SWW under orbital forcing from the mid-Holocene (7 kyr BP) to pre-industrial modern times (250 yr BP) is examined with transient experiments using the comprehensive coupled global climate model CCSM3. In addition, a model inter-comparison is carried out using orbitally forced Holocene transient simulations from four other coupled global climate models. Analyses and comparison of the model results suggest that the annual and seasonal mean SWW were subject to an overall strengthening and poleward shifting trend during the course of the mid-to-late Holocene under the influence of orbital forcing, except for the austral spring season, where the SWW exhibited an opposite trend of shifting towards the equator.